EFFECT OF BIO-RESIDUES AS HEAVY METAL IMMOBILIZERS IN CUCUMBER AND IRRIGATION WATER AT JAKARA, KANO - Abubakar, M. S.; Nasidi, N. M.; Shanono, N. J.; Zakari, M. D.; Sabo, A. A.; Ibrahim, A.; Shittu, S. K. (FUDMA JOURNAL OF SCIENCES, 2023)
Heavy metal contamination is a common problem in areas where industrial effluents are being discharged into the irrigation water. Farmlands along the Jakara River were not exceptions in which high concentrations of heavy metals are reported. This study was intended to evaluate the effect of some selected bio-residues: rice husk, groundnut shell, millet chaff, and sawdust for immobilization of heavy metals on cucumber crops at Jakara irrigated farm. Irrigation water samples were first collected and treated with rice husk and groundnut shell before application to the farm to understand the best treatment material. Similarly, the soil was treated with various quantities of the bio-residues, applied with irrigation water, and allowed for one week to achieve full decomposition of the materials. Thereafter, the cucumber seeds were planted in each treated plot and control plot. The results show that a rice husk of 1.5 g/l is the best bio-residue for water irrigation water treatment. It was found the concentrations of heavy metals in the cucumber yields were reduced by about 34% in the plot treated with 1.5 g/m2 of rice husk bio-residue. Moreover, both the Soil-to-cucumber Transfer Coefficient and Bio-residual Performance Index revealed that there is a highly significant effect of the application of bio-residual materials in managing the concentration of heavy metals in the cucumber yields.
Keywords: Bio-residual Performance Index; Groundnut Shell; Millet Chaff; Rice Husk; Soil-to-Cucumber Transfer Coefficient